Economic and Financial Feasibility Analysis on the Masterplan of the Sadai Industrial Estate (KIS) Bangka Belitung Islands Province - Sulistari Sulistari; Nizwan Zukhri; Hendrian Hendrian (Budapest International Research and Critics University, 2022)
In order to determine the economic and financial feasibility of the Sadai Industrial Estate (KIS), it is necessary to conduct an economic feasibility analysis and a financial feasibility analysis of the project. Analysis of the economic feasibility was performed using the production approach, the income approach, and the expenditure approach. A financial feasibility analysis was carried out using the Payback Period (PP), Average Rate of Return (ARR), Net Present Value (NPV), Profitability Index (PI), and Internal Rate of Return (IRR) methods. From the results of the analysis, it can be concluded that the development of the Sadai industrial area is economically and financially feasible.